2014
DOI: 10.1038/aps.2014.70
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin enhances swimming endurance of sedentary rats partially by regulation of antioxidant pathways

Abstract: Arctigenin efficiently enhances rat swimming endurance by elevation of the antioxidant capacity of the skeletal muscles, which has thereby highlighted the potential of this natural product as an antioxidant in the treatment of fatigue and related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…XO is an enzyme that catalyzes the oxidation of hypoxanthine to xanthine and could generate reactive oxygen species, leading to oxidative stress (Ardan et al, 2004). On the other hand, the p53, a tumor-suppressor protein, exhibits antioxidant activities to eliminate oxidative stress and ensure cell survival in response to low levels of oxidative stresses through the p53-regulated gene GPX1, manganese superoxide dismutase (MNSOD) or other pathways (Sablina et al, 2005;An et al, 2008;Liu and Xu, 2011;Chen et al, 2012;Wu et al, 2014). As we expected, the transcript level of XO in mice treated with B10 being obviously down-regulated compared with HFD group, p53 expression is markedly up-regulated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…XO is an enzyme that catalyzes the oxidation of hypoxanthine to xanthine and could generate reactive oxygen species, leading to oxidative stress (Ardan et al, 2004). On the other hand, the p53, a tumor-suppressor protein, exhibits antioxidant activities to eliminate oxidative stress and ensure cell survival in response to low levels of oxidative stresses through the p53-regulated gene GPX1, manganese superoxide dismutase (MNSOD) or other pathways (Sablina et al, 2005;An et al, 2008;Liu and Xu, 2011;Chen et al, 2012;Wu et al, 2014). As we expected, the transcript level of XO in mice treated with B10 being obviously down-regulated compared with HFD group, p53 expression is markedly up-regulated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously, hypoxia is also associated with energy metabolism (11). 5'-AMP-activated protein kinase (AMPK) is a key regulator of cellular and whole body energy balance (12). It acts to suppress anabolic ATP-consumption pathways, and stimulates catabolic ATP-generating pathways (13).…”
Section: Introductionmentioning
confidence: 88%
“…Due to their chemical structure, phytoestrogens can be classed as isoflavones and lignins. Arctigenin (Ar, Figure 1) is a lignin phytoestrogen extracted from Arctium lappa (Gao, Li, Zhang, & Zeng, 2008) that displays anti-inflammatory (Gao, Yang, & Zuo, 2018), antioxidant (Wu et al, 2014), antifibrosis (Lin et al, 2019), and antitumor effects (Maxwell, Chun, Lee, Kim, & Nam, 2017). In preliminary experiments, we found that arctigenin promotes the differentiation of bone marrow mesenchymal stem cells (BMSCs) of ovariectomized (OVX) rats into osteoblasts, leading to anti-osteoporosis effects.…”
Section: Introductionmentioning
confidence: 99%